RECOMMENDATION FOR AUTHORIZATION OVERLAPING OF PLACEMENT OF INDONESIAN FISHING VESSELS CREWS ABROAD - Muhammad Nur (Jurnal IUS Kajian Hukum dan Keadilan, 2018)
This normative juridical study examines the arrangement of fishing vessel crew placement from Indonesia to foreign countries which has been regulated by more than one institution. However, in the implementation of these institutions did not coordinate with each other which ultimately led to chaotic management in this sector. The fact that has been going on shows that the government is contributing to maintaining bad practices in placing and protecting the fishing vessel crew. This is based on overlapping arrangements regarding of placement and protection of fishing vessel crew. The issue that arises is related to which Ministry’s rule is must be obeyed? or the executor must submit to all rules of all existing ministries? The chaos of that authority ultimately gives rise to sectoral ego of each institution that feels authoritative in this sector. This situation has implications for the protection of fishing vessel crew and the concerns of companies involved in this business sector. Through this research is expected to contribute solutions to solve the problem of chaotic management of fishing vessel crew placement abroad.